Freedoms of expression, political extremismand seditious speech in the United States Supreme Court’s jurisprudence (Part II) - Machaj, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article constitutes the second part of a series devoted to analyzing the jurisprudence of the Supreme Court of the United States with respect to the First Amendment’s guarantee of freedom of expression and politically extremist speech. The author discusses the seminal case of Schenckv. United States wherein Justice Oliver Wendell Holmes established the famous “clear and present danger” standard as a means to determine the constitutionality of legislation pertaining to speech. The test allowed for criminalization of expression which had been deemed to cause such a peril. The article analyzes the original meaning of the standard, pointing out its speech-restrictive impact.
Keywords: First Amendment; freedom of speech; Supreme Court of the United States; clear and present danger; Oliver Wendell Holmes